Human parasitism by the exotic tick Dermacentor variabilis (Parasitiformes: Ixodida) in Brazil: report of an imported case - Martins,Thiago Fernandes (2022)
Abstract In June 2012, a tick was found parasitizing a man in the city of São Paulo, who had recently returned from a visit to Pennsylvania, in the northeast of the United States. The tick was removed and sent to the São Paulo State Department of Health, where it was identified as a male of the species Dermacentor variabilis (Say, 1821), according to the literature and taxonomic keys. The tick was subjected to a PCR test to search for rickettsiae, but the result was negative. The fact that a human entered Brazilian territory unaware that he was parasitized by a hard tick not belonging to the national tick fauna is significant because of the possibility that an exotic species could be introduced and take hold in this country. Another major risk to public health is that this arthropod could be infected with the bacterium Rickettsia rickettsii, as this ectoparasite is the main vector of Spotted Fever on the East Coast of North America.